Tuning emission and bandgap dynamics of MAPbBr₃ single crystals through halide exchange with methyl iodide - Dr. Md. Jahidul Islam; Md. Hafizul Islam (Chemical Physics Impact)
In this study we explore the chemical kinetics of spontaneous halide exchange reaction of methyl ammonium lead bromide micro crystal by incorporating iodide solution in hexadecane solvent. For this purpose, microscopic crystals methylammonium lead bromide (MAPbBr₃) were synthesized using solvent evaporation from the precursor solution of MABr and PbBr₂ dissolved in DMF. The resulting square shape crystals, characterized by their m3m space group with lattice constant 5.95 Ao and orange coloration in visualization, exhibited a bandgap of 2.26 eV, a broad absorption having transmittance edge at 540 nm, and a green photoluminescence emission peak at 540 nm. Halide exchange reactions were performed on these crystals by exposing them to methyl ammonium iodide as the source of iodide ion in the hexadecene solvent, leading to gradual changes in emission color from green to yellow and eventually red, corresponding to emission peak redshifts from 540 nm (2.30 eV) to 730 nm (1.7 eV). Kinetic analysis revealed that as iodide ions replaced bromide ions, the bandgap shifted progressively, with notable changes occurring within 15 min. The reaction dynamics were modeled to determine its order. A linear relationship between log of concentration and reaction time indicated first-order kinetics, with a regression value of 0.958. The rate constant of this reaction was calculated as 0.1049 (Minute)-1, and the reaction's half-life was determined to be 6.6 min. The study of this halide exchange kinetics in hybrid lead halide perovskites is crucial for understanding and controlling the optoelectronic properties of these materials. By understanding the reaction mechanisms and rates, it is possible to fine-tune the composition and morphology of perovskites, leading to improved device performance. Additionally, studying halide exchange kinetics can provide insights into the degradation mechanisms of perovskite materials, enabling the development of strategies to enhance their long-term stability.